2019
DOI: 10.3329/birdem.v9i1.39721
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Burnout Syndrome in an Intensive Care Unit of a Tertiary Care Hospital in Dhaka, Bangladesh

Abstract: Background: Burnout syndrome is a psychological term resulting from prolonged exposure to job stressors. It is a very common problem among health professionals especially intensive care unit (ICU) staffs (physicians, nurses, ward-attendant), as ICUs are characterized by a high level of work related stress. The consequences associated with professional burnout affect both the healthcare professionals and recipients. Methods:This cross-sectional study was done over the period of four months (April to July, 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…A meta-analysis found that the global prevalence of burnout among nurses is 11.23% 25 . Additionally, a cross-sectional study in Bangladesh reported that most ICU personnel, especially nurses, experience burnout to some extent 26 . Chin et al 27 conducted a study in Taiwan, which reported that higher levels of burnout and perpetual work stress are the main contributors to nurses considering suicide ideation.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis found that the global prevalence of burnout among nurses is 11.23% 25 . Additionally, a cross-sectional study in Bangladesh reported that most ICU personnel, especially nurses, experience burnout to some extent 26 . Chin et al 27 conducted a study in Taiwan, which reported that higher levels of burnout and perpetual work stress are the main contributors to nurses considering suicide ideation.…”
Section: Introductionmentioning
confidence: 99%
“…Among them there are some noteworthy publications from India [17][18][19][20] , Sri Lanka [21][22][23][24] , Pakistan [25][26][27][28][29] ,Nepal 30,31 and Bangladesh. 32,33 However till now there has not been any publication on multicenter studies involving medical personnel working in critical care units of any of South Asian countries.…”
mentioning
confidence: 99%
“…In one single center study done in 2017 from Bangladesh 33 96.7% study subjects (N 93) comprising doctors, nurses and ward attendants, suffered from moderate to high EE (Emotional Exhaustion) and 61.3% had been suffering from moderate to high DP (Depersonalization) and 81.7% scored high on PA (Personal Achievement) subscale.…”
mentioning
confidence: 99%